Differences in individual demographic factors in the public accountant's ethical judgment process - Anwar, Yuli (The Accounting Journal of Binaniaga, 2019)
This research aims to examine the differences in individual demographic factors in the public accountant's ethical judgment process in Indonesia. Data collected using purposive sampling and total of the samples is 301 respondents of accountants in Indonesia. The Result, revealed that: (a) there is no difference in ethical judgment of public accountants based on age, gender, experience, and status and (b) there are differences in ethical judgment of public accountants based on education level. These results revealed that public accountants in carrying out their duties and obligations as external auditors in private and government companies have no difference in terms of ethical judgment when deciding matters related to the audit they are undergoing due to age, gender, experience, and status. The difference in ethical judgment of public accountants in carrying out their duties and obligations when deciding matters related to deciding audit work will be different between public accountants who have S3 and S2 education with S1 and D3. Ethical judgment carried out by those with S3 and S2 education will be more careful in deciding because if it is wrong it will have an impact on the future. Keywords: Demographic Factors, Public Accountant, Ethical Judgment